Faktor-Faktor yang Berhubungan dengan Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Pekerja - Annisa Rahayu; Indah Restiaty; Catur Puspawati; Atang Saputra; Wakhyono Budianto (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2026)
In Indonesia, occupational safety and health (K3) issues are still often ignored. One of the main causes of occupational accidents is the lack of information on the implementation of K3. The ILO estimates that 2 million lives per year are claimed as a result of work accidents. Based on observations and interviews, ACTEM has several machines in the spinning to dyeing department that pose a high risk to the safety of workers, and still has workers who have not implemented K3. This research is an analytical descriptive research with a cross-sectional method with the title “Factors Associated with the Application of Occupational Safety and Health (K3) to Workers at PT Acryl Textile Mills (ACTEM) in 2024”. This study aims to identify and analyze the factors associated with the application of occupational safety and health (OHS) in workers at PT ACTEM in 2024. The population in this study was workers in the spinning and dyeing department of PT ACTEM. The sample of this study amounted to 91 workers. Data were collected using a structured questionnaire and observation sheets. The data were then processed through editing, coding, data entry, and cleaning, and analyzed univariately and bivariately using the chi-square test. Based on the results of the study using the chi-square test, it was found that there were 2 variables that had no relationship with the application of K3, namely compliance with company regulations and K3 counseling. Meanwhile, the variables of K3 knowledge, K3 commitment, and work environment supervision show that there is a relationship with K3 implementation.